Cell-free translation of influenza virus mRNA. - Content, J (1976)
Cytoplasmic poly (A)-rich RNA extracted from fowl plague virus-infected cells was found to program efficiently the translation of two major peptides in the wheat germ cell-free system. These peptides have the same electrophoretic mobility, on polyacrylamide gels, as the two major virion proteins M and NP. [35S] methionine tryptic peptide analysis by one-dimensionalthin-layer ionophoresis and finger printing by two-dimensional thin-layer ionophoresis and chromatography show a high degree of similarity between the two in vitro products and the authentic viral proteins M and NP. Although virion RNA is devoid of any poly (A) sequence, it is confirmed here that the viral complementary cytoplasmic RNA contains poly (A) stretches of varying lengths. Intact purified virion was found to promote the synthesis of very low amounts of the same NP and M proteins in this cell-free system. Quantitative aspects of data would indicate that this is due to minute amounts of complementary viral RNA associated with the virion or with the virion RNA itself. In conclusion, it is shown diectly by cell-free translation of authentic viral products that the influenza virion is "negative stranded" (Baltimore, 1971), at least for its two major structural proteins.